Improving Teacher Quality with the Effectiveness of Training for Private Elementary School Teachers in Bogor District - Griet Helena Laihad; Rais Hidayat; Sutji Harijanto (Jurnal Multidisiplin Sahombu, 2023)
Teacher quality is the quality level of a teacher in providing education by taking into account the capabilities of each individual or student which aims to obtain a standard reference in improving the quality of the learning process . The effectiveness of training is very important, especially for developing human resources, including teachers. This study aims to analyze the improvement of teacher quality with the effectiveness of training for private elementary school teachers in Bogor Regency. This study used a qualitative approach with descriptive analysis. The research results show that one of the efforts to improve teacher quality is to conduct effective training for teachers, especially in terms of developing their human resources by relying on four effectiveness measures, namely reaction, teaching process, behavior change and results. The expected output from the effectiveness of this training is that teachers can encourage active participation of students, promote learning processes that develop a culture of reading and writing in students and so on.